2000
DOI: 10.1021/ed077p1224
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Students' Thinking Patterns in Learning Organic Chemistry by the Use of Knowledge Space Theory

Abstract: Students' thinking patterns in learning organic chemistry were tracked through the one-year course taught to a total of approximately 1300 students, mostly biology majors, for a period of 2 years. As expected, the students' knowledge base increases, but the cognitive organization of the knowledge is surprisingly weak and misconceptions persist even after two years of college chemistry. Both a simple analysis of percentage of correct responses on pretests and posttests and establishing the connectivity of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 10 publications
(13 reference statements)
0
83
1
2
Order By: Relevance
“…Two authors [16] introduce their students to electrostatic potential surfaces in the hope that a sound understanding of electronegativity and resonance will enable the students to identify the negative and positive areas of molecules. A common misconception identified in their study was a "belief that bond polarities depend on several concepts.…”
Section: Covalent and Ionic Bonds And Electronegativitymentioning
confidence: 99%
See 3 more Smart Citations
“…Two authors [16] introduce their students to electrostatic potential surfaces in the hope that a sound understanding of electronegativity and resonance will enable the students to identify the negative and positive areas of molecules. A common misconception identified in their study was a "belief that bond polarities depend on several concepts.…”
Section: Covalent and Ionic Bonds And Electronegativitymentioning
confidence: 99%
“…A common misconception identified in their study was a "belief that bond polarities depend on several concepts. The belief was in the absolute electronegativities of atoms only, whether they are connected or not (e.g., hydrogen will always be positively charged)" ( [16], p. 1227). Students did not seem to appreciate that "polarity is a reflection of differences in electron distribution" ( [16], p. 1227).…”
Section: Covalent and Ionic Bonds And Electronegativitymentioning
confidence: 99%
See 2 more Smart Citations
“…There are different types of methods such as open-ended questions (Canpolat, 2006), three-tier tests (Milenkovic et al, 2016), concept mapping (Hazel & Prosser, 1994), drawings (Köse, 2008) and interviews (Şendur, 2012;Gercek, 2018) for detecting misconceptions in students of various levels. In the literature, although in a number of studies misconceptions have been reported in organic chemistry (Taagepera & Noori, 2000;Taber, 2002;Bryan, 2007;Anderson & Bodner, 2008;Domin, Al-Masum & Mensah 2008;Ferguson & Bodner, 2008), misconceptions related to subdomain of stereochemistry are very limited (Krylova, 1997;Lyon, 1999;Rushton et al, 2008, Mdachi, 2012.…”
Section: Introductionmentioning
confidence: 99%